Children who kill : profiles of pre-teen and teenage killers / Carol Anne Davis. - Davis, Carol Anne (Allison & Busby, 2003)
In this work, Carol Anne Davis explores the actions and motivation of 13 killers aged between 10 and 17. Well known cases including those of Mary Bell, Robert Thompson and John Venables are examined alongside historical case studies and lesser known crimes.